2015
DOI: 10.1002/hbm.22990
|View full text |Cite
|
Sign up to set email alerts
|

The controversial existence of the human superior fronto‐occipital fasciculus: Connectome‐based tractographic study with microdissection validation

Abstract: The superior fronto-occipital fasciculus (SFOF), a long association bundle that connects frontal and occipital lobes, is well-documented in monkeys but is controversial in human brain. Its assumed role is in visual processing and spatial awareness. To date, anatomical and neuroimaging studies on human and animal brains are not in agreement about the existence, course and terminations of SFOF. To clarify the existence of the SFOF in human brains, we applied deterministic fiber tractography to a template of 488 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 30 publications
4
42
0
Order By: Relevance
“…Of note, previous authors have suggested a lack of evidence for a superior fronto-occipital fasciculus (Meola, Comert, Yeh, Stefaneanu, & Fernandez-Miranda, 2015;Ture, Yasargil, & Pait, 1997). Consequently, some authors have used occipito-frontal fasciculus in place of IFOF (Makris et al, 2007;Reuter et al, 2009).…”
Section: Inferior Frontal-occipital Fasciculus Connectivitymentioning
confidence: 92%
“…Of note, previous authors have suggested a lack of evidence for a superior fronto-occipital fasciculus (Meola, Comert, Yeh, Stefaneanu, & Fernandez-Miranda, 2015;Ture, Yasargil, & Pait, 1997). Consequently, some authors have used occipito-frontal fasciculus in place of IFOF (Makris et al, 2007;Reuter et al, 2009).…”
Section: Inferior Frontal-occipital Fasciculus Connectivitymentioning
confidence: 92%
“…Additionally, the right SFO, which links frontal and parietal lobes, is associated with visuospatial functions [42]. In this context, it should be noted that a recent paper which employed both tractography and WM microdissection put forward the hypothesis that the SFO, whose anatomy is well-documented in monkeys, may not exist in the same form in human brains, hence prompting a reconsideration of the anatomical localization of brain functions classically associated with the SFO [43].…”
Section: Roi Label (Icbm-dti-81) Squared Modulus Of Roi Weights (%)mentioning
confidence: 99%
“…The automatic patient-specific tract identification was assessed as having very good colocalization with patient-specific fMRI activations. However, tractography methods are under active development (Jeurissen et al, 2014, Reisert et al, 2011, Tournier et al, 2012) and evaluation (Bucci et al, 2013, Fillard et al, 2011, Mormina et al, 2015, Neher et al, 2015, Pujol et al, 2015, Thomas et al, 2014), with many competing algorithms to choose from, and there remains significant anatomical controversy about the true extent and termination of many fiber tracts in the human brain (Dick and Tremblay, 2012, Meola et al, 2015, Von Der Heide et al, 2013) . Thus, there is unavoidable uncertainty in these and any other tractography results.…”
Section: Discussionmentioning
confidence: 99%